Peran Kepala Sekolah Dan Guru Pendidikan Agama Islam Dalam Mengatasi Kesulitan Siswa Membaca Al-Qur’an - Hikmah, Nur; Juhardi, Juhardi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The role of school principals and Islamic religious education teachers in overcoming students' difficulties in reading the Qur'an has become a hot topic recently. In essence, the role of school principals and teachers of Islamic religious education is very important to overcome student difficulties by providing adequate facilities and infrastructure and training students' fluency in reading the Qur'an because there are still many people who think schools with religious backgrounds are fluent in reading Al-Qur'an. Qur'an. Therefore, the researcher would like to discuss the role of school principals and Islamic religious education teachers in overcoming the difficulties of students reading the Qur'an at SMA Darul Ulum 3 Peterongan Jombang. The data collection procedure was carried out using the observation method, namely observing the learning process of the Qur'an and to find out the difficulties experienced by students. Both methods of interviews were conducted with principals, curriculum assistants, teachers, and students. The three documentation methods require a number of documents from informants to be used as the process of completing the research results. In this study the teacher has played a role in overcoming students who have difficulty reading the Qur'an. In overcoming students' difficulties in reading the Qur'an, the principals and teacher has a way, namely by providing facilities and infrastructure related to learning the Qur'an and special training for students who have difficulty reading the Qur'an outside of class hours.